2014
DOI: 10.1021/ic502358b
|View full text |Cite
|
Sign up to set email alerts
|

Low-Melting Imidazolium-Based Salts with the Paramagnetic Reineckate-Analogue Anion [Cr(NCS)4(bipy)](bipy = 2,2′-Bipyridine): Syntheses, Properties, and Structures

Abstract: In order to investigate the potential ionic liquid properties of Reineckate-analogue materials, four new salts, consisting of the heteroleptic [Cr(NCS)(4)(bipy)](-) complex anion and imidazolium-based cations A(+) = 1-ethyl-3-methylimidazolium, 1-n-butyl-3-methylimidazolium, pentamethylimidazolium, and 1,3-dimethyl-2,4,5-triphenylimidazolium, were investigated. Their structures were established by single-crystal X-ray diffraction. The compounds are paramagnetic with effective magnetic moments in the range of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Full information on all transitions are given in the Experimental section and maxima for compounds exhibiting the [Cr(NCS)6] -anion are found at 413 (416) and 552 (556) nm, for L = Pyr at 535 (543) nm, and for L = Pic at 537 (541) nm, respectively. These values closely resemble the ones found in the literature and the ligand field strength is also in accordance [31][32][33]56,58].…”
Section: Physicochemical Properties: Electronic and Infrared Datasupporting
confidence: 90%
See 2 more Smart Citations
“…Full information on all transitions are given in the Experimental section and maxima for compounds exhibiting the [Cr(NCS)6] -anion are found at 413 (416) and 552 (556) nm, for L = Pyr at 535 (543) nm, and for L = Pic at 537 (541) nm, respectively. These values closely resemble the ones found in the literature and the ligand field strength is also in accordance [31][32][33]56,58].…”
Section: Physicochemical Properties: Electronic and Infrared Datasupporting
confidence: 90%
“…The average Cr-N amine bond length equals 2.08 Å. The bond lengths are in good agreement with those found in other complexes with comparable complex anions [31][32][33][60][61][62][63]. The presence of extended hydrogen-bonding networks further influences the bond angles (see Table 3).…”
Section: Crystal Structuressupporting
confidence: 85%
See 1 more Smart Citation
“…6 Interestingly, studies on paramagnetic MCILs predate those works, but were focused on other aspects of the materials, disregarding their magnetic properties. 7,8 Subsequent to these studies, the magnetic properties of MCILs started attracting more attention, with reports of MCILs containing mononuclear magnetic cations, [9][10][11][12][13][14][15][16] mononuclear magnetic anions [17][18][19][20][21][22][23][24][25] and one report on the magnetic properties of a triferric cationic MCIL. 26 Due to the mononuclear structures of the spin carriers in those magnetic MCILs, the tuning of their magnetic properties, when attempted, focused on modifications of the diamagnetic counterion; e.g., it was demonstrated that changing the countercation charge, two or three [FeCl 3 Br] anions could be assembled around it, yielding a higher magnetic moment per formula unit.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, we have reported on different classes of transition metal-containing low-melting ILs with complex anions of the 3d metals Cr, Co, and Ni, respectively, of which a series of physicochemical data is available [24,25,26,27,28,29,30,31,32,33,34]. The astonishing results from imidazolium-based ILs containing the [Co(NCS) 4 ] 2− anion [25] led us to extending our research for new low-melting, transparent ILs which contain tetrahedrally coordinated manganese(II) complex anions which could also be suitable as catalysts in chemical reactions.…”
Section: Introductionmentioning
confidence: 99%